2022
DOI: 10.1002/kin.21620
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic adsorption of drugs using carbon nanofibers in simulated gastric and intestinal fluids

Abstract: Two different classes of drugs were selected to test the adsorption capacity of carbon nanofibers as a greener new generation alternative adsorbent in simulated gastric and intestinal fluids. Kinetics of the promethazine and trimethoprim adsorption were analyzed using Lagergren first order and Pseudo second order models. Intraparticle diffusion graphs were also plotted to discuss the adsorption mechanism. Kinetic data showed the significance of boundary layer effect for both of the drugs and the presence of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The conical-shaped carbon nanofibers (CNFs) have been investigated as a green alternative. Previous studies have demonstrated the efficient adsorption capability of CNFs for organic molecules in a stimulated gastric and intestinal medium [66]. The properties and characterization of CNFs have been published elsewhere, where it was reported that the CNFs used in this study are pyrolitically stripped, with an average diameter of 130 nm, an average pore volume of 0.12 cm 3 /g, an average pore diameter of 89.3 Å, and an average specific surface area of 54 m 2 /g, with a pHPZC value of 4.9 [43].…”
Section: Vd Loading and Preparation Of Aerogelsmentioning
confidence: 99%
“…The conical-shaped carbon nanofibers (CNFs) have been investigated as a green alternative. Previous studies have demonstrated the efficient adsorption capability of CNFs for organic molecules in a stimulated gastric and intestinal medium [66]. The properties and characterization of CNFs have been published elsewhere, where it was reported that the CNFs used in this study are pyrolitically stripped, with an average diameter of 130 nm, an average pore volume of 0.12 cm 3 /g, an average pore diameter of 89.3 Å, and an average specific surface area of 54 m 2 /g, with a pHPZC value of 4.9 [43].…”
Section: Vd Loading and Preparation Of Aerogelsmentioning
confidence: 99%